2021
DOI: 10.1051/e3sconf/202124611005
|View full text |Cite
|
Sign up to set email alerts
|

Energy flexibility potential of domestic hot water systems in apartment buildings

Abstract: Domestic Hot Water (DHW) storage tanks are identified as a main source of flexible energy use in buildings. As a basis for energy management in apartment buildings, this paper describes the aggregated DHW use in a case building, and analyses the potential for DHW energy flexibility by simulating different control options. The case study for the work is an apartment building in Oslo with 56 apartments and a shared DHW system. Energy measurements are available for consumed hot water, hot water circulation, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Alternatively, energy companies can pay a flexibility bonus per kWh of shifted demand. It has been shown that such incentives can greatly improve the return on investment [37,69]. However, too many incentives without regulation can lead to the use of less efficient technologies which offer greater flexibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, energy companies can pay a flexibility bonus per kWh of shifted demand. It has been shown that such incentives can greatly improve the return on investment [37,69]. However, too many incentives without regulation can lead to the use of less efficient technologies which offer greater flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…The study used measured DHW profiles recorded for 50 days. Sørensen et al [37] further developed this research by applying four rule-based control strategies to the measured data using a simplified tank model based on energy capacity. The four control strategies were peak power limitation; spot price saving where each day was divided into low, medium and high price periods; flexibility sale with no heating in peak periods; and maximising self-consumption of a photovoltaic system.…”
Section: Introductionmentioning
confidence: 99%